Pengaruh Pengembangan Karir dan Motivasi Kerja Terhadap Produktivitas Karyawan pada PT Mutiara Mulia Raya (Jurnal Riset Manajemen dan Akuntansi, 2025)
Employee productivity is an important factor in supporting the success of a company, especially in the mining industry, which has its own operational challenges. This study aims to analyze the influence of career development and work motivation on employee productivity at PT Mutiara Mulia Raya. This study uses a quantitative approach with a population of 113 employees and a sample of 76 people selected through purposive sampling. Data was collected through questionnaires and analyzed using multiple linear regression. The results indicate that career development and work motivation, both partially and simultaneously, have a positive and significant impact on employee productivity. These findings indicate that the better the management of career development and work motivation programs, the higher the resulting employee productivity. The implications of this study highlight the importance of company management in designing productivity improvement strategies through the provision of clear career paths and effective motivation systems. Companies are advised to continue developing human resource development policies to create a productive and highly competitive work environment.